Newer Treatment Modalities in Epidermolysis Bullosa - Bruckner-Tuderman, Leena (Indian Dermatol Online J, 2019)
The term epidermolysis bullosa (EB) refers to a group of hereditary skin blistering diseases. The group is clinically and genetically heterogeneous, but all EB forms are associated with mechanically induced skin blistering and fragility. The causative gene mutations of most EB types are known. The current international consensus classification contains four main types: EB simplex (EBS), junctional EB (JEB), dystrophic EB (DEB), and Kindler syndrome (KS). The classification is based on the morphological level of blister formation. In EBS, the split is intra-epidermal, in JEB along the basement membrane and in DEB below the basement membrane. In Kindler syndrome, the dermal-epidermal junction is disorganized, and blisters can occur on all three levels. Each major EB type has further subtypes which may differ in terms of their genetic, biological or clinical characteristics. Traditionally, EB treatments have been symptomatic, but increasing understanding of disease etio-pathogenesis is facilitating development of novel evidence-based therapy approaches. First gene- and cell-based therapies are being tested at preclinical level and in clinical trials. New knowledge on secondary disease mechanisms has led to development and clinical testing of urgently needed symptom-relief therapies using small molecules and biologicals.